Implementasi Private Cloud Storage Berbasis Debian Server Menggunakan Nextcloud Sebagai Sentralisasi Penyimpanan Data Pada CV Unelma Pictura - Ramdoni; Sahrul Bahri, Dede (CV. Shofanah Media Berkah, 2024)
The growth of digital companies such as Unelma Pictura has created a demand for efficient and secure data storage systems. Currently, data exchange activities rely heavily on personal devices, WhatsApp groups, and physical media such as flash drives and external hard drives. This leads to decentralized file management, low efficiency, and high data security risks. Therefore, a solution in the form of centralized data storage is needed to enhance productivity and security. This study implements Private Cloud Storage based on Nextcloud on Linux Debian as a centralized data storage solution. The method employed follows the Waterfall system development model, which includes analysis, design, installation, configuration, and system testing. Data collection techniques used in this research consist of observation, interviews, and literature review. The system is designed to be accessible through a local network via an IP address or a public network using a custom domain. The test results indicate that the implementation performs well and meets the company’s needs. Server testing with 2–4 PCs shows CPU usage increases from 22.9% to 45.1% during upload and from 3.1% to 7.2% during download, while memory usage remains stable. This system has proven to enhance efficiency, security, and productivity in the company's data management.